Biosekuriti Pasar Unggas Hidup dan Risiko Avian Influenza di Bogor: Implikasi Surveilans One Health - Hidayah, Dinda Nur; Sudarnika, Etih Etih Sudarnika; Pisestyani, Herwin; Agungpriyono, Srihadi (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Background: Live bird markets (LBMs) are critical nodes in the poultry supply chain but also high-risk environments for avian influenza (AI) transmission.Objectives: This study assessed biosecurity, sanitation, and environmental practices in LBMs in Bogor, Indonesia, and evaluated evidence of AI exposure in poultry through serological testing.Methods: A cross-sectional survey was conducted in nine LBMs using structured questionnaires and observations, alongside serological testing with the hemagglutination inhibition (HI) assay to detect antibodies against H5N1 clades 2.1.3 and 2.3.2.Results: Significant biosecurity gaps were identified, including reliance on motorcycles for poultry transport, mixing of birds from multiple sources and species, absence of wastewater treatment facilities, and frequent presence of stray animals. Serological testing detected antibodies in layer chickens (55.6% for both clades) and broilers (11.2% for clade 2.3.2), suggesting ongoing viral exposure potentially linked to vaccination and/or field circulation.Conclusions: The findings highlight LBMs as amplification points for AI, with implications for poultry health, human exposure, and environmental contamination. Strengthening biosecurity and market infrastructure, enforcing animal health certification, and implementing safe disposal of sick or dead birds are critical. Integrating these measures within a One Health framework is essential to reduce AI risks and enhance zoonotic disease preparedness in Indonesia.